LITERASI INFORMASI LINTAS BUDAYA KUNCI KESUKSESAN BERBASIS DARING (KOLABORASI DOSEN DAN ALUMNI) - Tamaela, Ida Costansa; Apituley, Patresya; Wenno, Eldaa Crystle (Universitas Pattimura, 2021)
The purpose of this webinar with the theme Interkulturelle Landeskunde, which is conducted virtually or online, is to provide information on how important cross-cultural communication is in building a good relationship with individuals or communities with different backgrounds. This webinar activity was attended by 2nd semester students who took Interkulturelle Landeskunde, numbered 18 peoples and high school or vocational students, namely from SMAN 9 Ambon, SMAN 4 Maluku Tengah, SMAN 1 Seram Bagian barat, SMAN 44 Maluku Tengah, and SMKS Tourism Pamahanunusa in Masohi, a total of 62 peoples. The methods used in this webinar activity are the presentation of material, questions, and answers, filling out questionnaires distributed during the webinar, and playing videos about German and its language knowledge. The questionnaire distributed contained questions related to the material provided by the speakers. At the end of the competition, there is a quick and precise competition in the form of a quiz for students. Students who can answer quickly and accurately are given prizes in the form of credit data. The webinar was carried out by presenting material by three German speakers, and three alumni of German Language Education Study Program students who were already working and living in Germany. And one lecturer of the German Language Education Study Program FKIP Unpatti who is currently studying further in Dresden (Germany). The results of the questionnaire answers obtained showed that the activities carried out succeeded in making students learn to continue their studies or work in Germany as well as important cross-cultural understanding.